1996
DOI: 10.3171/jns.1996.84.5.0879
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of a cerebral arteriovenous malformation after surgical excision

Abstract: Complete excision of a cerebral arteriovenous malformation (AVM) should eliminate the future risk of an associated intracranial hemorrhage. Because total removal of an AVM may be difficult to assess at the time of surgery, postoperative angiography has become the accepted standard for documenting that the removal has been accomplished. However, even angiography confirmed excision of an AVM does not completely ensure against rebleeding. Regrowth of an AVM with subsequent hemorrhage can occur. This has been docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 14 publications
2
50
1
Order By: Relevance
“…17,18 Several cases of AVM recurrence in the same location following some form of intervention (ie, gamma knife, excision, embolization, etc) have been reported in pediatric patients and adults. 19,20 Abnormalities of arterial 21 venous, 22 and microvascular 23 structures have been described in relation to areas of abnormal neuronal migration. Abnormal vascular structures have been described in association with periventricular nodular heterotopia in filamin 1 gene mutation, 23 suggesting 1 potential link between neuronal migrational disorders and vascular malformations.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Several cases of AVM recurrence in the same location following some form of intervention (ie, gamma knife, excision, embolization, etc) have been reported in pediatric patients and adults. 19,20 Abnormalities of arterial 21 venous, 22 and microvascular 23 structures have been described in relation to areas of abnormal neuronal migration. Abnormal vascular structures have been described in association with periventricular nodular heterotopia in filamin 1 gene mutation, 23 suggesting 1 potential link between neuronal migrational disorders and vascular malformations.…”
Section: Discussionmentioning
confidence: 99%
“…19) Previous cases of AVM recurrence after surgical excision and postoperative angiographic disappearance suggest that regrowth of the remnant arteriovenous shunt will result in development of de novo AVM nidus. 2,7) We speculate that development of the dural feeders might further enhance gradual growth of the nidus, resulting in homonymous hemianopia. Giant occipital AVMs might enlarge beyond the extent of the occipital lobe, becoming inoperable and incurable, and as a result, the severe migraine-like headaches and AVM will persist.…”
Section: Discussionmentioning
confidence: 99%
“…If more mature AVMs develop along a continuum as the brain develops, children are more likely to have immature vasculature as part of their AVM. Immature vessels left in the surgical bed may not be visible on angiography, but they may retain the ability to regrow and form a new malformation in the same location 5) . This hypothesis is supported by the findings of Klimo et al 11) , who reported that diffuse lesions were disproportionately represented in cases of failed obliteration, residual lesion, or recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Complete excision or obliteration of the lesion usually eliminates the risks of hemorrhage, and a negative cerebral angiogram is generally considered indicative of a cure. Although recurrence of cerebral AVMs is rare, there are several reports of cerebral AVM recurrence in both children 1,2,4,[9][10][11] and adults 3,5,8,16) after complete resection verified by postoperative angiography.…”
Section: Introductionmentioning
confidence: 99%